Current Developments in Production and Utilization of Biogas and Biomethane in Germany. Issue 1 (6th December 2017) - Daniel‐Gromke, Jaqueline; Rensberg, Nadja; Denysenko, Velina; Stinner, Walter; Schmalfuß, Tina; Scheftelowitz, Mattes; Nelles, Michael; Liebetrau, Jan
Abstract: This paper presents the results of a status quo analysis of biogas production in Germany. It provides detailed information regarding the biogas plant portfolio and distribution, applied technologies, types of substrates und the contribution of biogas to the electricity, heat and transport sector. The evaluations regarding biogas and biomethane are based on data from annually surveys of biogas plant operators, Federal Network Agency regarding electricity generation, German transmission grid operators regarding direct marketing of electricity, and the current plant register regarding flexibility premium. Abstract : This work provides general and detail information regarding biogas plant portfolio and distribution, applied technologies, kind of substrates, and the current contribution of biogas and biomethane within the electricity, the heat and the transport sector in Germany.